2005
DOI: 10.1111/j.1600-0420.2005.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Central corneal thickness in high myopia

Abstract: ABSTRACT.Purpose: To examine if central corneal thickness (CCT) is different in emmetropia and high myopia. Methods: 57 emmetropic subjects (0 to + 1.5 D) and 48 high myopes (all more than -6 D in spherical equivalent refraction) were studied. CCT was measured by a Haag-Streit Optical Low-Coherence Reflectometry (OLCR) pachymeter, a recently developed high precision pachymeter with a standard deviation (SD) for repeated measurements of 1 mm. Results: Mean CCT for the emmetropic group was 538.6 mm (SD = 32.1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 21 publications
3
30
2
3
Order By: Relevance
“…3,13 The correlation between refractive error and corneal thickness, in particular CET, has not yet been clearly established. [14][15][16][17] In high myopia, known changes occur in the posterior segment: staphyloma, myopic conus, choroidal atrophy, and thinning of the retina and sclera. 15 Owing to the longer eyeballs in high myopia, both the anterior and posterior segments can exhibit abnormalities.…”
mentioning
confidence: 99%
“…3,13 The correlation between refractive error and corneal thickness, in particular CET, has not yet been clearly established. [14][15][16][17] In high myopia, known changes occur in the posterior segment: staphyloma, myopic conus, choroidal atrophy, and thinning of the retina and sclera. 15 Owing to the longer eyeballs in high myopia, both the anterior and posterior segments can exhibit abnormalities.…”
mentioning
confidence: 99%
“…(4) Review of literature also indicates that decrease in corneal thickness in myopic patients is due to anterior segment change, as eyeball is elongated and emmetropes too had thinner Central Corneal Thickness. (4,5) Corneal thickness assist in determining various ophthalmic medical and surgical treatment such as corneal transplant, refractive surgical procedures, contact lens wear to prevent postoperative corneal thinning. In high myopes more stromal ablation is needed to achieve optical correction, which renders the postoperative cornea even thinner.…”
Section: Resultsmentioning
confidence: 99%
“…(4)(5)(6)(7)(8)(9) In preoperative assessment of candidates for LASIK residual, stromal thickness of 250 -300 microns must be ensured. Also optical zone in keratorefractive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…22 Although these studies used sample sizes of a few hundred or few thousand subjects, the trend of these previous data supports our speculation that a more equatorial latitude is associated with increased central corneal thickness, perhaps because of the increased intensity of sunlight and increased exposure to ultraviolet light. 23 We found that the thickness of the left eye was greater than the thickness of the right eye in multiple measures: central corneal thickness, corneal vertex thickness, and thinnest 26 reported that the thickness of the cornea in the right eye was thinner than in the left in low myopic people; they speculated that the difference may be due to the angle j. In our study, there were more residents from the Uygur ethnic group in Xinjiang, which is quite different from nationality of residents of the other three provinces, most of whom have reported Han nationality.…”
Section: Discussionmentioning
confidence: 99%